Joint distraction for the treatment of knee osteoarthritis - Thun Itthipanichpong; Ali Farooqi; Samarth V. Menta; Anil S. Ranawat (Journal of Cartilage & Joint Preservation, 2023)
Knee osteoarthritis (OA) is a common degenerative joint disease characterized by cartilage destruction and changes in subchondral bone. Treatment options for end-stage OA are limited, with joint replacement and high tibial osteotomy as the common procedures. High tibial osteotomy may be preferable to joint replacement in the young active patient, malaligned knee, and limited to medial compartment OA. However, both procedures may lead to complications and have durability concerns in young patients. Fortunately, joint distraction (JD) has emerged as a joint-preserving treatment for end-stage OA. The reversal of tissue degeneration observed with JD could be the result of one or more proposed mechanisms, such as partial unloading, synovial fluid pressure oscillation, mechanical and biochemical changes in subchondral bone, or adhesion and chondrogenic commitment of joint-derived mesenchymal stem cells. The procedure involves the use of an external fixator to unload the cartilage and underlying bone for a short time period. In addition, new implantable knee devices, which create unloading instead of distraction and do not require removal, have also been developed. There is a lack of standardization for the JD technique which results in significant variation of implant type, duration of treatment, and rehabilitation. Nevertheless, clinical studies demonstrate long-term pain relief and improved patient outcomes. Interestingly, the increase in joint space width following treatment indicates that cartilage repair occurred throughout and after the distraction period. Although JD appears to be an effective therapeutic choice, the rate of complications remains high, with pin-tract infection being the most common.